Préparation mentale en pôle espoirs rugby : impact sur les habiletés mentales, la motivation, le stress, la récupération et les blessures - Delauny, E.; Zamia, S.; Bouthier, S.; Ruffault, A. (Movement & Sport Sciences - Science & Motricité, 2020)
The aim of this study is to determine the impact of a mental skills training on mental skills, motivation, stress, recovery, and the occurrence of injuries among young elite rugby players. Twenty-four players participated in this study during one season. Four sessions including goal setting and attentional focus were delivered at the beginning of the season, following which a training diary was provided to the players. Goals were reviewed during a mid-season session. Mental skills, motivation, stress, and recovery in a sport setting were measured using questionnaires. Training diary use and occurrence of injuries were gathered prospectively. The results showed that the intervention has been followed by an increase in intrinsic motivation and sport-specific recovery strategies. However, second and third year players were seemed to benefit most from the intervention than new players. This study offers perspectives on individualized coaching in mental skills training as well as research on psychological and behavioral effects of such interventions.